PENGARUH PEMBERIAN BERBAGAI JENIS PROBIOTIK TERHADAP PERTUMBUHAN IKAN NILA MERAH (Oreochromis sp.) - Nur A’isah; Tri Yusufi Mardiana (Fakultas Perikanan Universitas Pekalongan, 2017)
The Purpose of this research was to know the different probiotics types giving effect to highest growth on red tilapia fish (Oreochromis sp.). This research was held on 1st November 2015 until 30th November 2015 at brackish water and sea Laboratory, Fisheries Faculty, Pekalongan University. Method was using experiment method with completely randomized design (RAL) consisting of 4 treatments and 3 replications. The fourth treatments are treatment A (without probiotic), treatment B (commercial probiotic 1), treatment C (commercial probiotic 2) and treatment D (tuber Banana’s probiotic). Each treatments with given probiotic dose 10 cc/kg feed. Red tilapia fish sized 3-5 cm to the aquarium stocked at a density of 1fish/liter. The paramete orbserved were the growth rate, survival rate (SR), and water quaity. The result shows that the different probiotics given were effect on red nile tilapia growth (F count > F Tabel). Probiotic from commercial probiotic 1 gave the highest result on red nile tilapia fish weight growth were 7.02 grs. Tuckey test result shows that treatment B – treatment A very significant effect on red tilapia weight growth with value 3.043 (5% = 0.829, 1% = 1,086). Red tilapia fish survival rate during research reach 100%. Water quality research good to red nile fish culture medium, were temperature 26 – 29o C, pH 6.7 – 7.8 , and DO 6 mg/l.Keyword : Red Tilapia Fish, Probiotics, Growth